“Condensating into vivid portraits”: l’intertestualità nascosta nella poesia di Medbh McGuckian - Gamerra, Gioia (Studi irlandesi. A Journal of Irish Studies, 2011)
The following essay aims at investigating the semantic and intertextual denseness of McGuckian’s poems, going beyond her supposed incommunicability. She has often highlighted the “balancing” and “clarifying” power of her own poems, and the unbiased reader will realise that they do contain an immediate and outspoken quality. This is often mysteriously conveyed by certain images which emerge from the intermingling of textual and intertextual places. Usually, in many of her works, McGuckian quotes or refers to wide parts of some texts, whose source is not indicated. Sometimes her poems rise from the way these fragments are interwoven, even without any ‘new’ word, in order to define and confirm a contemporary and intimally feminine poetical identity. This essay will discover and enlighten some of these intertextual processes and devises, which, necessarily, add meaning to her already semantically and iconographically dense poetic visions.